Serial analysis of gene expression (SAGE) of hostplant resistance to the cassava mosaic disease (CMD) - Fregene, Martin A.; Matsumura, H.; Akano, A.; Dixon, A.; Terauchi, R. (Springer, 2004)
Cassava mosaic disease (CMD) is a viral disease of the important tropical staple crop cassava (Manihot esculenta) and preferred management involves use of host–plant resistance. The best available resistance is controlled by a single dominant gene. Serial analysis of gene expression (SAGE) was used to analyze the gene expression pattern in a bulk of 40 each of CMD resistant and susceptible genotypes drawn from a gene mapping progeny. Messenger RNA used for the SAGE analysis came from plants that were exposed to heavy disease pressure over a period of 2 years in the field. A total of 12,786 tags were studied, divided into 5733 and 7053 tags from the resistant and susceptible genotypes, respectively. Tag annotation was by PCR amplification using the tag sequence as sense primer and 4000 cassava ESTs generated from the bulk of CMD resistant genotypes. Annotation of more than 30 differentially expressed tags revealed several genes expressed during systemic acquired resistance (SAR) in plants and other genes involved in cell-to-cell and cytoplasm-to-nucleus virus trafficking. Differential expression of the most abundantly expressed tag, corresponding to a beta-tubulin gene, was confirmed by Northern Analysis. RFLP analysis of the tags in the parents and bulks of the CMD mapping progeny revealed only one tag, a WRKY transcription factor, associated with the region bearing the dominant CMD gene.